Enlightenment, Modernization, Professional Training: Count György Festetics’s Role in Establishing Agricultural Higher Education in Hungary at the End of the Eighteenth Century - Kurucz, György (Historical Studies on Central Europe, 2022)
Western historical narratives of the Enlightenment tend to depict the eighteenth-century aristocracy as a unique promoter of overall progress, whereas Hungarian historiography is more inclined to appraise their role according to a deprecating approach based on the criticism of a traditional class system. However, it seems clear that a more balanced judgement of the Hungarian aristocracy should involve a complex analysis. In first place, it is to be decided whether erudite and financially well-off individuals existed, and if so, to what extent they were willing and capable of contributing to various forms of innovation, let alone social and cultural progress. For this reason, this paper is designed to focus on the activities of Count György Festetics, a Transdanubian Hungarian aristocrat who was educated in the Theresianum, an elite Viennese training institute, but whose career prospects were thwarted at the end of the eighteenth century on account of his involvement with the anti-Habsburg movement of Hungary’s lesser nobility on the death of Emperor Joseph II. This analysis seems justifiable, because Festetics’s decision to set up a farming college in Keszthely clearly shows his commitment to progress, aiming at the adaptation of modern methods as well as creating the institutional background for the dissemination of specialist knowledge among the various layers of contemporary society.